Detection rate of prostate cancer following biopsy among the northern Han Chinese population: a single-center retrospective study of 1022 cases - Yong Jia; Lei-Yi Zhu; Yu-Xin Xian; Xiao-Qing Sun; Jian-Gang Gao; Xin-Hong Zhang; Si-Chuan Hou; Chang-Cun Zhang; Zhao-Xu Liu (World Journal of Surgical Oncology, 2017)
Abstract Background Prostate cancer is known to have ethnic and regional differences. The study aimed to clinically evaluate the detection rate of prostate cancer on transrectal ultrasonography (TRUS)-guided prostate biopsy and analyze its characteristics among the northern Han Chinese population at a single center. Methods Between October 2009 and September 2016, a total of 1027 Chinese men, who had undergone TRUS-guided prostate biopsy at Qingdao Municipal Hospital, were retrospectively analyzed. Prostate biopsies were performed in the case of an abnormally elevated serum PSA level, and/or abnormal digital rectal examination (DRE) findings, and/or suspicious prostatic imaging findings. Results Of the 1022 men enrolled in the analysis, 438 patients (42.8%) were diagnosed with prostate adenocarcinoma histologically. When serum PSA levels were divided into five subgroups (less than 4.0, 4.0 to 10.0, 10.0 to 20.0, 20.0 to 100.0, and ≥ 100.0 ng/ml), the detection rates of prostate cancer were 12.4, 15.9, 34.1, 66.2, and 93.8%, respectively. With serum PSA levels of 4.0 to 10.0 ng/ml, the cancer detection rates for a normal DRE and a suspect DRE finding were 13.5 and 58.2%, respectively. Accordingly, the cancer detection rates for a normal imaging and a suspect imaging finding were 13.5 and 58.2%, respectively. Besides, a large proportion of the patients were in the clinically advanced stage. Conclusions The present study data reported a relatively higher prostate cancer detection rate of 42.8% and that the majority of the patients presented with clinically advanced prostate cancers within a local clinical urologic practice. An early detection and screening program for prostate cancer is of great need to reduce the burden from this disease among the northern Han Chinese population.